Література та культура Полісся. – Вип. 85 - (:unkn) unknown (My University, 2016)
Literature and Culture of Polissya. – Vol. 85. Series “History Research”. – № 6 / editor-in-chief H. V. Samoylenko. – Nizhyn : NDU named after Gogol, 2016. – 273 с.